¿Es el español “área lingüística arcaica”? - Nowikow, Wiaczesław (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
In the case of Romance languages, there are three factors which determine the degree of linguistic archaism or innovation: 1) the geographical position (Bartoli); 2) contact with other languages (Iordan) and 3) the time of Romanization (Cano Aguilar, Penny). The aim of this paper is the determination of the degree of archaism and innovation of the Spanish language in comparison with other Romance languages. At the end of this article, there is an analysis of the phonological, grammatical and lexical changes and features of the Spanish language.